Memories of old Manila (NCCA, 1993)
A short, syncretic vision of a city that was once the envy of the Orient but has now sunk into despair - Manila. In this short film, a historian (Behn Cervantes) travels through time from the swampland that was once the city into the squalor that it has become on contemporary time. In between these scenes is five centuries that define Manila as the country's premier city. As the historian revisits major periods of its history, he too is transformed and affected by what he sees and what he knows. In the swampland that was the beginning and is now the end of the city, time collapses past and present, memory and consciousness, as he drowns in a quagmire of historical forgetfulness and remembrance."--Center for New Cinema Website.